Influência da forma de contato inicial e preaquecimento na camada intermetálica no processo de soldagem por fricção de materiais dissimilares - Marlon Antônio Pinheiro (2021)
Friction welding is a solid-state welding process and has as its main joining mechanism, diffusion and mechanical mixing. The process is presented as an option, as it generates less residual stress, less distortion and cracks. The characteristics of the process also allow satisfactory welding of dissimilar materials, with good results in terms of mechanical strength. However, welding dissimilar materials is a challenge, given the differences in properties between two materials, in addition to the possible formation of intermetallic compounds. The objective of this study was to investigate the butt welding by conventional rotary friction of aluminum ASTM A6351 T6 and SAE 1020 steel. The experiments sought to evaluate the effects of the initial contact geometry and preheat of the steel at 300ºC in the structures, mainly in the possible formation of compounds intermetallic and the consequences in terms of mechanical strength of welded joints. To meet the objectives of this work, it was necessary to develop a conventional friction welding machine and an induction preheating device. Preliminary tests were carried out, validated by tensile tests and metallographic tests of welded joints. After preliminary tests, welds and tensile, microhardness, metallographic and X-ray diffraction tests were produced, which confirmed that the use of aluminum conical tips and flat steel tips at room temperature favor the mechanical performance of the welds. While welding, using aluminum conical tips, with steel preheating to 300 ° C, causes a reduction in tensile strength. It was observed that in the preheated samples there was an increase in the intermetallic layer, in addition to increasing the presence of cracks and discontinuities. It was also found that there was no formation of intermetallic compounds that would justify the substantial reduction in the tensile test results.